2018
DOI: 10.1080/02770903.2017.1369988
|View full text |Cite
|
Sign up to set email alerts
|

Association between daily ambient air pollution and respiratory symptoms in children with asthma and healthy children in western Japan

Abstract: Our results suggest that using long-term medications to manage asthma may play an important role in preventing exacerbation of respiratory symptoms due to air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…We failed to explain any association of local differences in air pollution from the traffic with either symptoms or COPD, as both CAT, mMRT scores, and COPD prevalence were similar in those living in the first, second, third or even fifth row of houses from the major road. Outdoor air pollution in studies elsewhere consistently showed greater likelihood of respiratory symptoms in both children and adults [24][25][26][27] and COPD. [8][9][10] We hypothesize, that the basic air pollution level in Almaty is so high, that a distance of 50 to 100 meters from a major road cannot play a role in worsening the symptoms.…”
Section: Figurementioning
confidence: 88%
“…We failed to explain any association of local differences in air pollution from the traffic with either symptoms or COPD, as both CAT, mMRT scores, and COPD prevalence were similar in those living in the first, second, third or even fifth row of houses from the major road. Outdoor air pollution in studies elsewhere consistently showed greater likelihood of respiratory symptoms in both children and adults [24][25][26][27] and COPD. [8][9][10] We hypothesize, that the basic air pollution level in Almaty is so high, that a distance of 50 to 100 meters from a major road cannot play a role in worsening the symptoms.…”
Section: Figurementioning
confidence: 88%
“…This may be mainly because of two reasons: first, children's low immune function makes them more susceptible to respiratory infections, and second, previous studies have shown that air pollution may lead to increased respiratory diseases in children. [8][9][10] The Global Burden of Disease 2013 study found that lower respiratory tract infections were the leading cause of hospitalization for children aged 0-19 years in most developing countries, and particularly among children younger than 5 years. 11 Many of the risk factors for respiratory diseases, such as household air pollution and low immunity, are avoidable through proper prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…Optimising an individual's level of asthma control may influence respiratory response to in-vehicle exposures during rush-hour commuting, with one study in the USA showing that the largest post-commute increases in exhaled nitric oxide occurred in participants with below-median asthma control, and higher PM 2.5 was associated with a lower forced expiratory volume in 1 s percentage predicted in this group [183]. Among Japanese children with asthma, exacerbation of respiratory signs and symptoms ( percentage maximum peak expiratory flow and coughing) associated with oxidant exposure from ambient air pollution appeared greater in those who were not using long-term medications than those who were [184].…”
Section: Background and Evidencementioning
confidence: 83%